Theoretical Investigation of the Sliding Instability and Caving Depth of Coal Wall Workface Based on the Bishop Strip Method - Chao Li; Tianhe Kang; Xiaopo Li; Ligong Li; Xiaoyu Zhang; Runxu Zhang (Advances in Civil Engineering)
As mining height increases, the influence of coal wall caving on safety production becomes stronger. There is no systematic and effective method to analyse the risk of coal wall caving and its slip caving depth. First, this paper established the Bishop mechanical model of sliding instability of coal wall, and then it deduced the general equation of a safety factor for every slip surface, which can be used to judge the stability of the coal body on the slip surface. Moreover, taking the 8102 workface in the Wulonghu Mine, China, as an example, this paper evaluated the calculation method of slip surface safety factor in detail and obtained the critical slip surface position and the maximum slip depth of a coal wall. Overall, the results showed that the maximum slip depth based on the Bishop strip method is more consistent with the measured data compared with other methods and thus has strong significance and practical engineering value for selecting the most suitable method and its parameters of regulating coal wall caving.